Manual de seguridad y salud del trabajo en los Laboratorios Agropecuarios de la ESPAM MFL. - Doumet Chancay, Karen Verónica (2015)
The diagnosis of conditions of occupational health and safety of the activities carried out by the staff of the laboratories of the agricultural area of the ESPAM MFL is the overall objective of this research. It was defined by four stages that served as a basis for general assessment of working conditions, starting from the site of the work environment to the activities that generated the recognition of the presence of risk factors present and exposed to workers. Manual application of Occupational Safety and Health presents labor standards to minimize risks to safeguard the integrity of labor, presenting through the Occupational Risk Matrix links with the different risk factors in the performance of any activity labor, it will allow further assessing of risks in each process and achieving study so each unit have precautionary measures done by the Occupational Safety Manager.